Simultaneous Controllability for a System with Resistance Term - ANTUNES, G.O.; ARARUNA, F.A.; MEDEIROS, L.A. (Trends in Computational and Applied Mathematics, 2002)
In this work we study the simultaneous controllability for a system of equations that constitutes a model of dynamical elasticity for incompressible materials.